1995
DOI: 10.1016/0144-8617(95)00088-7
|View full text |Cite
|
Sign up to set email alerts
|

The kinetics of the acetylation of gelatinised potato starch

Abstract: The reaction rates, in the base-catalysed acetylation of gelatinised aqueous starch (4 wt%), by vinylacetate (ViAc), were investigated in a semibatch reactor at temperatures ranging from 20 to 50°C. The desired starch acetylation reaction is accompanied by an undesired parallel base-catalysed hydrolysis reaction of vinylacetate and a consecutive hydrolysis reaction of the acetylated starch. The rate equations are: Starch acetylation: &AC =-k, cvic CRO-Starch acetate hydrolysis: &A= =-kz CRAM con-Vinylacetate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 11 publications
0
22
0
1
Order By: Relevance
“…Kinetic data on the acetylation of potato starch in a slurry system had been reported by Jetten et al [7] and the rates of the acetylation reactions of potato starch using vinil acetate had been reported by de Graaf et al [3]. However, no data have been published on the rates of the acetylation reactions of gadung flour (GF) with glacial acetic acid (GAA).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…Kinetic data on the acetylation of potato starch in a slurry system had been reported by Jetten et al [7] and the rates of the acetylation reactions of potato starch using vinil acetate had been reported by de Graaf et al [3]. However, no data have been published on the rates of the acetylation reactions of gadung flour (GF) with glacial acetic acid (GAA).…”
Section: Introductionmentioning
confidence: 94%
“…Thus, the rate of acetic acid decomposition: (4) From previous studies of the acetylation of potato starch with vinyl acetate, de Graaf et al [3] reported that acetylation reaction was first order both in starch and acetyl. …”
Section: Reaction Of Acetic Acid With Starch At Reaction Surfacementioning
confidence: 99%
See 2 more Smart Citations
“…Modified starches are used in numerous applications and industrial processes (de Graaf, Broekroelofs, Janssen, & Beenackers, 1995). One of these applications is the use of benzylated starch as paper finisher (Wurtzburg, 1986).…”
Section: Introductionmentioning
confidence: 99%